Expression, refolding and crystallization of murine MHC class I H-2D(b) in complex with human β(2)-microglobulin - Sandalova, Tatyana (International Union of Crystallography, 2005)
β(2)-Microglobulin (β(2)m) is non-covalently linked to the major histocompatibility (MHC) class I heavy chain and interacts with CD8 and Ly49 receptors. Murine MHC class I can bind human β(2)m (hβ(2)m) and such hybrid molecules are often used in structural and functional studies. The replacement of mouse β(2)m (mβ(2)m) by hβ(2)m has important functional consequences for MHC class I complex stability and specificity, but the structural basis for this is unknown. To investigate the impact of species-specific β(2)m subunits on MHC class I conformation, murine MHC class I H-2D(b) in complex with hβ(2)m and the peptide gp33 derived from lymphocytic choriomeningitis virus (LCMV) has been expressed, refolded in vitro and crystallized. Crystals containing two complexes per asymmetric unit and belonging to the space group P2(1), with unit-cell parameters a = 68.1, b = 65.2, c = 101.9 Å, β = 102.4°, were obtained.